2011
DOI: 10.1124/jpet.110.175786
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phosphatidylinositol 3-Kinase/Akt Signaling Pathway Mediates Acquired Resistance to Sorafenib in Hepatocellular Carcinoma Cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most common potentially lethal human malignancies worldwide. Sorafenib, a tyrosine kinase inhibitor, was recently approved by the United States Food and Drug Administration for HCC. In this study, we established two sorafenib-resistant HCC cell lines from Huh7, a human HCC cell line, by long-term exposure of cells to sorafenib. Sorafenib induced significant apoptosis in Huh7 cells; however, Huh7-R1 and Huh7-R2 showed significant resistance to sorafenib-induced apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
229
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(240 citation statements)
references
References 27 publications
9
229
1
1
Order By: Relevance
“…4A), even when phosphorylation of AKT was increased by sorafenib treatment in HepG2 and Huh7 cells (Fig. 4A); this is consistent with results reported by other groups 5. Notably, the level of phosphorylated ERK was not further decreased by ceritinib in HCC cells treated with a combination of ceritinib and sorafenib compared to such cells treated with sorafenib alone (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…4A), even when phosphorylation of AKT was increased by sorafenib treatment in HepG2 and Huh7 cells (Fig. 4A); this is consistent with results reported by other groups 5. Notably, the level of phosphorylated ERK was not further decreased by ceritinib in HCC cells treated with a combination of ceritinib and sorafenib compared to such cells treated with sorafenib alone (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Although sorafenib inhibits multiple kinase activities to suppress tumor angiogenesis and proliferation, other signaling pathways, such as PI3K/AKT, which sorafenib does not inhibit at low or even higher doses, contribute to cell growth and survival in sorafenib‐acquired resistant cells 5. The IGF1R signal pathway has been reported to be enriched in sorafenib‐acquired resistant tumor cells 27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was used in renal cell carcinoma first, which prolongs neutral progression free survival time from 2.8 months to 5.5 months (Escudier et al, 2007). Based on further investigation, sorafenib improves the survival of patients with advanced hepatocellular carcinoma (HCC) (HuitzilMelendez et al, 2008;Chen et al, 2011). In the present paper, OS, TTP, TTSP, DCR and adverse reactions in clinical randomized controlled trials were summarized and assessed to confirm the efficacy of sorafenib in HCC therapy, providing clinical practice guidelines of evidencebased-medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is largely cytostatic (6), suggesting that intrinsic resistance is more common in tumors, although some reports describe tumor shrinkage upon sorafenib treatment (7). Studies involving HCC cell lines or immunohistochemical staining of tumor sections revealed that sorafenib resistance correlates with the up-regulation of several signaling pathways, including the mammalian target of rapamycin (mTOR) pathway as assayed by S6 S235/236 (8) and Akt S473 phosphorylation (9). Other potential resistance mechanisms involve epithelial-to-mesenchymal transition (EMT) and autophagy (10, 11).…”
mentioning
confidence: 99%